Prevalence of Uropathogenic E. Coli, Antimicrobial Susceptibility Profiles and Carriage of Extended-Spectrum Beta-Lactamases Genes at Mama Lucy Hospital, Kenya - Chelangat, Shirleen; Ngugi, Caroline; Song’oro, Edinah; Mwaniki, John (Global Journal of Health Sciences, 2025)
Purpose: Urinary tract infection (UTI) is a common bacterial infection affecting millions worldwide. Escherichia coli (E. coli) is the most prevalent causative agent of UTIs. This study aimed to determine the prevalence, antimicrobial susceptibility profiles and carriage of ESβL resistance genes among uropathogenic E. coli recovered from adults at Mama Lucy Hospital. Methodology: A cross-sectional study was conducted. A purposive method was used to obtain 347 urine samples from patients who presented with symptoms suggestive of UTI and were cultured for E. coli using cysteine lactose electrolyte-deficient agar and eosin methylene blue agar. The collected urine samples were also subjected to dipstick analysis and microscopy. Questionnaires were used to collect sociodemographic data and possible risk factors for urinary tract infections. The recovered isolates were identified using conventional biochemical tests. Antimicrobial susceptibility profiles were determined using the Kirby diffusion disc method. The occurrence of ESβLs, including TEM, OXA, SHV, and CTX-M, was determined by polymerase chain reaction (PCR). Findings: The overall prevalence rate of UTIs was 23.7%, whereas the E. coli prevalence rate was 13.3%. The isolates presented high levels of resistance to trimethoprim-sulfamethoxazole (81.3%), amoxicillin-clavulanic acid (66.7%), ciprofloxacin (62.5%), tetracycline (60.4%), ceftriaxone (54.2%), and cefoxitin (54.2%), whereas they were more susceptible to meropenem (14.6%), chloramphenicol (12.5%), and nitrofurantoin (8.3%). A total of 25 of the 46 E. coli isolates were screened for ESβL genes. TEM was the most common gene21/25 (84%), SHV12/25 (48%), OXA 7/25 (28%), and CTX-M 18/25 (66.1%), which indicates a high frequency of β-lactamase gene production among UTIs causing E. coli. Unique Contribution to Theory, Practice and Policy: Based on these findings, current treatment guidelines should be revised to prevent increasing antimicrobial resistance through continuous surveillance, screening for extended-spectrum beta-lactamase genes, routine culture and antibiotic sensitivity testing. Additionally, the prevalence of UTIs should be continuously monitored to monitor trends that form a basis for preventive and treatment guidelines, such as policy development and prudent use of antibiotics, to reduce the increasing UTI burden in the population.